Examining the Root Causes of On-Street Parking Mismanagement in Central Bangkok - Chullabodhi, Chakaphan; Chalermpong, Saksith; Ratanawaraha, Apiwat (Nakhara : Journal of Environmental Design and Planning, 2022)
Bangkok, a sprawling metropolis and capital of Thailand, has long-struggled with chronic on-street parking mismanagement despite repeated government attempts at regulation. This paper examines the root causes of ineffective on-street parking management in the city, elicited using root cause analysis (RCA), documentary research, field surveys, and in-depth interviews as data sources. In-depth semi-structured interviews were conducted with fifteen government officers, focusing on the mindsets, motivations and incentives of stakeholders, and tree diagrams were developed to visualize cause-and-effect relationships and identify root causes of mismanagement. Our analysis identified eight root causes of ineffective on-street parking management stemming from misalignment of government bodies, including a fragmented institutional framework, lack of interest and commitment from both national and local policymakers, the limited legislative authority of the local government, lack of on-street parking policy, lack of planning and review, ineffective law and regulation enforcement, lack of monitoring mechanisms, and low perceived seriousness of parking infringements. Based on these findings, several priority action steps are proposed to help policymakers in effectively managing on-street parking in Bangkok.